PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH,KETERLIBATAN SISWA DAN KURIKULUM TERHADAP HASIL BELAJAR SISWA DENGAN LINGKUNGAN BELAJAR SEBAGAI VARIABEL INTERVENING - Ottar, Zuhroh Sadeptusia; Yulasmi, Yulasmi; Lusiana, Lusiana (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study aims to analyze the influence of School Principal Leadership Style, Student Engagement, and Curriculum on Learning Environment and Learning Outcomes in schools. The sample used in this study consists of 100 respondents, including teachers and students. Data were collected using questionnaires and analyzed with the SmartPLS application to test the relationships between variables. The results of the study indicate that: (1) there is a significant influence of the School Principal Leadership Style on the Learning Environment; (2) there is a significant influence of Student Engagement on the Learning Environment; (3) there is a significant influence of Curriculum on the Learning Environment; (4) there is a significant influence of the School Principal Leadership Style on Learning Outcomes; (5) there is a significant influence of Student Engagement on Learning Outcomes; (6) there is a significant influence of Curriculum on Learning Outcomes; (7) there is no significant influence of the Learning Environment on Learning Outcomes; (8) the Learning Environment does not mediate the relationship between School Principal Leadership Style and Learning Outcomes; (9) the Learning Environment does not mediate the relationship between Student Engagement and Learning Outcomes; and (10) the Learning Environment does not mediate the relationship between Curriculum and Learning Outcomes. These findings provide valuable insights for educational management, particularly in the roles of school leadership, student engagement, and curriculum implementation in creating an environment that supports optimal learning outcomes.